Sexual arousal by dominance and submission in relation to increased reproductive success in the general population - Jozifkova, Eva; Kolackova, Martina (Neuro endocrinology letters, 2017)
OBJECTIVE: Sexual arousal by dominance and submissiveness was long considered a mental disorder. The origin of this sexual preference has not been clearly explained. This study scrutinizes the hypothesis that sexual arousal by hierarchical disparity is a manifestation of mating strategy by comparing number of offspring and self-reported attractiveness of the study participants. METHODS: Our data were obtained from the general population via e-mail questionnaire (n=673, age 25-34 years and 35-44 years). RESULTS: Sexually dominant men aged 35-44 years had more biological male children. Both the sexually dominant men aged 35-44 years and sexually submissive women aged 35-44 years perceived themselves as being more attractive. THE MAIN FINDINGS: Here we show that sexual arousal by dominance and submissiveness confers an increased capacity to pass on genes in the general population. CONCLUSION: We suggest that sexual arousal by dominance is likely to be the means by which the mating strategy is accomplished. Sexual arousal by dominance and submissiveness is a manifestation of mating strategy because such a behaviour results in an increased reproductive success and thus may lead to the preferential selection of individuals who prefer sexual arousal by hierarchical disparity. This fact explains why the high number of people is excited by sexual fantasies and activities connected to hierarchical disparity. This finding might open up novel insights into some reproductive medicine issues, as well as into such field as partnership therapy and partner violence.
Keywords: Female; sebepojetí; dominance a subordinace; Dominance-Subordination; mužské pohlaví; emoce; Humans; Self Concept; dospělí; Libido; Reproduction; Sex Factors; lidé; rozmnožování; sexuální chování; sexuální faktory; ženské pohlaví; Sexual Behavior; Adult; Emotions; libido; Male